The Relationship between Violation of the Psychological Contract and Intention to Leave Work (A Field Study on Nurses in Private Hospitals in Homs City) - مريش, ماريا; فداء ناصر (Latakia University Journal - Economic and Legal Sciences Series, 2025)
This study aimed to identify the impact of psychological contract violation on intention to leave in private hospitals in Homs City. The descriptive and analytical approach was employed as it suits the nature of the study, aiming to achieve a comprehensive and accurate description of the study topic, data collection and analysis, and hypothesis testing. The study sample consisted of nurses from three hospitals in Homs City (Al-Muzaina, Farzat Ayyoub, and Ahli), where 110 questionnaires were distributed to the sample, and 100 valid questionnaires were retrieved for analysis, resulting in a sample size of 100 nurses. The most significant findings of this study were: The majority of the research sample agree that the hospital they work for has violated the psychological contract between them. The majority of the research sample have the intention to leave their current job in the hospital. The majority of the research sample strongly disagree that they suffer from emotional burnout. There is a direct relationship between psychological contract violation and intention to leave, as an increase of one unit leads to an increase in intention to leave by 0.837 units.